Does Clinical Practice in Psychiatric Nursing Change Students’ Perspectives on Psychiatric Nursing and Mental Illnesses?: A Qualitative Study - Ferhan Açıkgöz; Aysel Karaca (Sakarya Üniversitesi Holistik Sağlık Dergisi, 2026)
Objective: This study aims to examine students’ perspectives on individuals with mental disorders and psychiatric nursing before and after the psychiatric nursing clinical course, as well as their thoughts and experiences regarding the clinical practice, using a qualitative approach.Methods: A qualitative research method was employed in this study, and data were collected through focus group interviews. In this study, three separate focus group interviews were conducted, each consisting of 10 participants. The data from the focus group interviews were subjected to thematic analysis to identify key themes and patterns.Results: Four themes were identified: perceptions regarding mental disorders; judgments about clinical practice (related to the clinical environment, patients, and students’ own competencies); willingness to become a psychiatric nurse; and levels of anxiety associated with clinical practice.Conclusions: At the end of the clinical practice, students’ negative perceptions of mental illnesses decreased. The psychiatric nursing course presents an opportunity for students to recognize and transform their negative attitudes toward mental disorders.